High-irradiation-resistant cooling window with graded metamaterial structure coating as well as preparation method and application of high-irradiation-resistant cooling window

By integrating a graded metamaterial structural coating on the window frame and the surface of the shutter blades, the existing windows have insufficient ability to regulate solar radiation and its own thermal radiation, effectively controlling the indoor temperature and reducing the indoor temperature by 8.05℃.

CN119664224AActive Publication Date: 2025-03-21HUAZHONG UNIV OF SCI & TECH +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411840157.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

Existing windows lack the ability to regulate solar radiation and their own thermal radiation, and cannot achieve immediate control of indoor temperature.

Method used

High-irradiation-resistant cooling windows with graded metamaterial structural coatings are adopted. By integrating graded metamaterial structural coatings on the window frames and the surface of the blinds blades, the spectral regulation performance is optimized and solar radiation reflection and mid-infrared radiation emission capabilities are improved.

Benefits of technology

Significantly reduce the absorption of external solar radiation heat by windows, and adjust the indoor temperature through strong mid-infrared radiation emission, achieving effective control of indoor temperature and reducing the indoor temperature by 8.05℃.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119664224A_ABST
    Figure CN119664224A_ABST
Patent Text Reader

Abstract

The invention provides a high-irradiation-resistant cooling window with a graded metamaterial structure coating and a preparation method and application of the high-irradiation-resistant cooling window. According to the high-irradiation-resistant cooling window, at least one graded metamaterial structure coating is integrated on the surfaces of a window outer frame and louver blades, and the high-irradiation-resistant cooling window with the graded metamaterial structure coating is formed. The graded metamaterial structure coating comprises a light function layer and a cover face hydrophobic protection layer which are designed through a graded micro-nano structure, the reflection path of solar irradiation in the coating can be effectively and accurately regulated, and the efficient high-irradiation-resistant performance of the cooling window is achieved. The high-irradiation-resistant cooling window can realize sustainable, efficient and passive cooling in a high solar irradiation environment. The high-irradiation-resistant cooling window can be suitable for windows of office buildings, sentry boxes and other buildings, windows of vehicles such as automobiles, trains, airplanes and steamships and windows of special equipment such as space capsules, and the indoor thermal comfort of the buildings, the vehicles, the special equipment and the like in the high-solar-irradiation environment is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building materials, and in particular to a high-irradiation resistant cooling window with a graded metamaterial structure coating, and a preparation method and application thereof. Background Art

[0002] As people's living standards continue to improve, people's requirements for living environment are getting higher and higher, and intelligent environmental control technology is becoming more and more closely related to people's daily lives. Indoor light intensity and temperature are two important indicators that determine the comfort level of the building environment. Windows are the channels for buildings to directly exchange light and heat with the external environment. Regulating the heat radiation exchange between the indoor and the environment through windows is an effective way to adjust the indoor environment. Therefore, windows have always been the focus of architectural design and interior decoration. Existing window fixtures such as curtain gauze, sunshade curtains, curtains, and blinds are the most common window components. However, traditional window fixtures currently only control the isolation and connection between the indoor and external environment through simple opening and closing actions. They do not have the ability to regulate the reception of solar radiation and their own heat radiation emission, and cannot achieve instant regulation of indoor temperature.

[0003] Prior art CN202110780815.6 discloses a cooling product, which is composed of a full solar spectrum high-reflection film with micro-nano pores formed by winding and interweaving multiple micro-nano fibers and a base material, and the full solar spectrum high-reflection film is composited on the refrigeration base cloth to obtain a full solar spectrum high-reflection fabric; Prior art CN202311450217.8 also discloses a preparation method and application of passive cooling photothermal regulation fibers and fabrics; it designs the micro-nano optical structure of the fiber, utilizes the difference between different refractive indices inside the fiber to achieve high reflection of the solar radiation band, and combines the imaginary part of the refractive index properties of the fiber material and the introduced nano-medium particles to achieve high emission in the entire mid-infrared band, thereby realizing wide-spectrum selective regulation of passive cooling photothermal regulation fibers and fabrics in the solar radiation band and the mid-infrared band, and ultimately achieving efficient passive cooling effect on the human body in high temperature outdoor environments. Patent CN 116104253A discloses a thermal insulation color steel tile and its preparation method, which solves the problem of high temperature of thermal insulation color steel plate by stacking multiple anti-corrosion layers, waterproof layers, aerogel layers and radiation cooling layers. However, its structure is diverse, the preparation process is relatively complicated, multiple types of solvents are required and the maintenance cycle is long, which is not suitable for application on the surface of window building materials.

[0004] The purpose of regulating spectral performance is achieved by adding optical particles into the polymer matrix of the window surface coating. This method has a performance upper limit. In order to obtain better spectral characteristics, the material properties are very demanding, and blindly changing the proportion of material components can easily destroy the material performance. Therefore, it is of great inventive significance to seek a new method that can improve the performance of cooling materials as much as possible without changing the material composition and maintaining the material properties. However, previous technologies often only process and combine materials without finely optimizing the materials, which results in the failure to achieve the highest optical performance when using similar raw materials. Summary of the invention

[0005] In view of this, a high-irradiation resistant cooling window with a graded metamaterial structure coating and a preparation method and application thereof are proposed. The graded metamaterial structure coating is integrated into the window frame and the surface of the shutter blades to form a high-irradiation resistant cooling window with a graded metamaterial structure coating, which significantly reduces the window's absorption of external solar radiation heat and emits its own heat into the environment as strong mid-infrared radiation, thereby solving the problem of weak thermal regulation ability of windows in the prior art.

[0006] The present invention provides a high-irradiation resistant cooling window with a graded metamaterial structure coating, the high-irradiation resistant cooling window comprising: a first glass, a second glass, a shutter and two window frames;

[0007] The first combination of the high-radiation resistant cooling window is a first glass, a second glass, a shutter and two window frames, the first glass and the second glass are arranged at intervals, and the shutter is located between the first glass and the second glass; the first glass, the second glass and the shutter are all fixed between the two window frames;

[0008] The second combination of the high-irradiation resistant cooling window is a first glass, a second glass, a shutter and two window frames, wherein the first glass and the second glass are arranged at intervals, the shutter is located outside the second glass or the first glass, and the first glass, the second glass and the shutter are all fixed between the two window frames;

[0009] At least one graded metamaterial structure coating is integrated on the surface of the shutter or window frame.

[0010] Preferably, the hierarchical metamaterial structure coating comprises a base layer, an optical functional layer having a microscopic hierarchical micro-nano structure, and a top hydrophobic protective layer stacked in sequence;

[0011] The optical functional layer with microscopic hierarchical micro-nano structure comprises a first high molecular polymer and a first high refractive index inorganic spectral particle filler.

[0012] Preferably, one side surface of the bottom layer is bonded to the surface of the window frame or the shutter blade, and the other side surface is bonded to the optical functional layer of the microscopic hierarchical micro-nano structure;

[0013] The bottom layer comprises an organic second macromolecular polymer and a functional filler;

[0014] The second high molecular polymer includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polychlorotrifluoroethylene, acrylic resin, epoxy resin, polyurethane, polyester resin, vinyl resin and silicone resin;

[0015] The functional filler includes an anti-corrosion filler and a second high refractive index inorganic spectral particle;

[0016] The anti-corrosion filler comprises at least one of zinc powder, hexasodium phosphate, ferric oxide, zinc phosphate and aluminum tripolyphosphate;

[0017] The second high-refractive inorganic spectral particle filler includes at least one of titanium dioxide, silicon dioxide, barium sulfate, aluminum oxide, zinc oxide, silicon carbide, zinc sulfide, boron nitride, magnesium oxide, barium carbonate and aluminum silicate.

[0018] Preferably, the first high molecular polymer includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polychlorotrifluoroethylene, acrylic resin, epoxy resin, polyurethane, polyester resin, vinyl resin and silicone resin;

[0019] The first high-refractive inorganic spectral particle filler comprises at least one of titanium dioxide, silicon dioxide, barium sulfate, aluminum oxide, zinc oxide, silicon carbide, zinc sulfide, boron nitride, magnesium oxide, barium carbonate and aluminum silicate;

[0020] The mass fraction of the first high-refractive inorganic spectral particle filler in the optical functional layer is 20 to 50%;

[0021] The particle size of the first high-refractive inorganic spectral particle filler is 10nm to 5000nm;

[0022] Inside the optical functional layer with microscopic hierarchical micro-nano structure, in the thickness direction, the size of the first high refractive index inorganic spectral particle filler is distributed in a regular pattern from large to small or from small to large;

[0023] Inside the optical functional layer with microscopic hierarchical micro-nano structure, in the thickness direction, the volume fraction of the first high refractive index inorganic spectral particle filler is distributed in a regular pattern from large to small or from small to large.

[0024] Preferably, the surface hydrophobic protective layer comprises a third high molecular weight polymer and a hydrophobic filler, and a third high refractive inorganic spectral particle filler;

[0025] The third high molecular polymer includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polychlorotrifluoroethylene, acrylic resin, epoxy resin, polyurethane, polyester resin, vinyl resin and silicone resin;

[0026] The hydrophobic filler includes at least one of a silane coupling agent, an organic silicon resin, and nano silicon dioxide.

[0027] The third high-refractive inorganic spectral particle filler includes at least one of titanium dioxide, silicon dioxide, barium sulfate, aluminum oxide, zinc oxide, silicon carbide, zinc sulfide, boron nitride, magnesium oxide, barium carbonate and aluminum silicate;

[0028] The mass fraction of the third high-refractive inorganic spectral particle filler in the overcoat hydrophobic protective layer is 5-10%.

[0029] Preferably, the thickness of the optical functional layer of the microscopic hierarchical micro-nano structure is 50 μm to 200 μm;

[0030] The thickness of the bottom layer is 10 μm to 100 μm;

[0031] The particle size of the second highest refractive index inorganic spectral particles in the bottom layer is 10nm to 5000nm;

[0032] The particle size of the anti-corrosion filler is 200nm to 5000nm;

[0033] The thickness of the hydrophobic protective layer on the cover surface is 5 μm to 100 μm;

[0034] The particle size of the third high-refractive inorganic spectral particle filler in the overcoat hydrophobic protective layer is 10nm to 5000nm.

[0035] Preferably, the bottom layer, the optical functional layer with microscopic hierarchical micro-nano structure, and the top hydrophobic protective layer further include a diluent, and the diluent is xylene;

[0036] The bottom layer includes a second high molecular polymer and a xylene diluent, the second high molecular polymer includes a fluororesin and an acrylic resin, and the mass ratio of the fluororesin, the acrylic resin, and the xylene is (15-20): (5-10): (25-35);

[0037] Or, the bottom layer includes a second high molecular polymer, an anti-corrosion filler, and xylene, the second high molecular polymer includes fluororesin and acrylic resin, the mass ratio of the fluororesin, acrylic resin, xylene, and anti-corrosion filler is (15-20): (5-10): (25-40): (60-75); the anti-corrosion filler is zinc powder; the particle size of the anti-corrosion filler is 200nm-5000nm;

[0038] Or, the bottom layer includes a second high molecular polymer, an anti-corrosion filler, xylene, and a second high refractive index inorganic particle, the second high molecular polymer includes a fluororesin and an acrylic resin, the mass ratio of the fluororesin, the acrylic resin, the xylene, the anti-corrosion filler, and the second high refractive index inorganic particle is (15-20): (5-10): (25-40): (60-75): (5-10); the second high refractive index inorganic particle is titanium dioxide, and the particle size of the second high refractive index inorganic particle is 100nm-500nm.

[0039] Preferably, the optical functional layer with microscopic hierarchical micro-nano structure comprises a plurality of mutually superimposed sub-optical functional layers, each of which comprises a first high molecular polymer, a first high refractive index inorganic spectral particle, and xylene, the first high molecular polymer comprises a fluororesin and an acrylic resin, and the particle size and mass ratio of the first high refractive index inorganic spectral particle in different sub-optical functional layers are different;

[0040] The first high refractive index inorganic spectral particles include at least one of titanium dioxide with a particle size of 100nm to 500nm, titanium dioxide with a particle size of 500nm to 800nm, and titanium dioxide with a particle size of 800nm ​​to 1400nm;

[0041] The mass ratio of the fluororesin, acrylic resin, xylene and the first high refractive index inorganic spectral particles is (55-65): (15-25): (60-70): (10-80).

[0042] Preferably, the overlay hydrophobic protective layer comprises a third high molecular weight polymer and xylene, the third high molecular weight polymer comprises a fluororesin and an acrylic resin, and the mass ratio of the fluororesin, the acrylic resin, the xylene, and the hydrophobic particles is (55-65): (15-25): (70-80): (10-25);

[0043] Or, the cover hydrophobic protective layer includes a third high molecular weight organic polymer, xylene, and a third high refractive index inorganic spectral particle filler, the third high molecular weight organic polymer includes fluororesin and acrylic resin, and the mass ratio of the fluororesin, acrylic resin, xylene, and the third high refractive index inorganic spectral particles is (55-65): (15-25): (70-80): (10-25): (15-20); the third high refractive index inorganic spectral particles are aluminum oxide with a diameter of 100nm to 300nm.

[0044] Preferably, the optical functional layer with microscopic hierarchical micro-nano structure is composed of two sub-optical functional layers, namely, a bottom optical functional layer and an upper optical functional layer, from bottom to top;

[0045] Wherein, the first high refractive index inorganic spectral particles in the upper optical functional layer are titanium dioxide with a particle size of 100nm to 500nm;

[0046] The first high refractive index inorganic spectral particles in the bottom optical functional layer are titanium dioxide with a particle size of 500nm to 800nm;

[0047] Or, the optical functional layer with microscopic hierarchical micro-nano structure includes three sub-optical functional layers, an upper optical functional layer, a middle optical functional layer, and a bottom optical functional layer, from bottom to top;

[0048] The first high refractive index inorganic spectral particles in the upper optical functional layer are titanium dioxide with a particle size of 100nm to 500nm;

[0049] The first high refractive index inorganic spectral particles in the middle optical functional layer are titanium dioxide with a particle size of 500nm to 800nm;

[0050] The first high refractive index inorganic spectral particles in the bottom optical functional layer are titanium dioxide with a particle size of 800nm ​​to 1400nm;

[0051] Or the first high refractive index inorganic spectral particles in the optical functional layer include a mixture of titanium dioxide with a mass ratio of (3-7): (1-3): (1-3) with particle sizes of 100nm-500nm, 500nm-800nm, and 800nm-1400nm respectively.

[0052] In a second aspect, the present invention further provides a method for preparing the high-irradiation-resistant cooling window with a graded metamaterial structure coating, wherein the first glass, the second glass, and the blinds are all installed between the window outer frame to obtain a cooling window with a graded metamaterial structure high-irradiation-resistant coating;

[0053] Wherein, at least one graded metamaterial structure coating is integrated on the surface of the shutter or window frame;

[0054] The method for preparing the hierarchical metamaterial structure coating comprises the following steps:

[0055] Adding optional second high refractive index inorganic spectral particles, optional anti-corrosion filler, and optional diluent to the second high molecular polymer, stirring and mixing, to obtain a bottom layer mixture;

[0056] Apply the primer mixture to the surface of the window frame or shutter blades to form a primer;

[0057] Adding a first high refractive index inorganic spectral particle filler with different physical properties and an optional diluent into a first high molecular polymer, stirring and mixing, to obtain a plurality of spectral functional mixtures;

[0058] Applying a plurality of spectral functional mixtures in sequence on the surface of the bottom layer to form a light functional layer with a microscopic hierarchical micro-nano structure;

[0059] Adding the optional third high-refractive inorganic spectral particles, hydrophobic material, and optional diluent to the third high molecular weight polymer, stirring and mixing, to obtain a surface hydrophobic protective layer mixture;

[0060] The surface hydrophobic protective layer mixture is coated on the surface of the optical functional layer with microscopic graded micro-nano structure to form the surface hydrophobic protective layer.

[0061] In a third aspect, the present invention also provides an application of the high-irradiation resistant cooling window with a graded metamaterial structure coating or the high-irradiation resistant cooling window with a graded metamaterial structure coating prepared by the preparation method in office buildings, factories, residential buildings, sentry boxes, mobile homes, glass curtain walls, exhibition halls and commercial centers, as well as cars, trains, airplanes, ships and yachts, as well as space capsules, drones, armored vehicles, fighter jets and helicopters.

[0062] The cooling window with a graded metamaterial structure high-irradiation resistant coating and the preparation method thereof of the present invention have the following technical effects compared with the prior art:

[0063] 1. The high-irradiation cooling window with graded metamaterial structure coating of the present invention is formed by integrating the graded metamaterial structure coating on the window frame and the surface of the blinds, which significantly reduces the window's absorption of external solar radiation heat and emits its own heat into the environment as strong mid-infrared radiation. The graded metamaterial structure coating includes a bottom layer, an optical functional layer, and a cover hydrophobic protective layer. The size and volume fraction of the micro-nano structure are graded and designed so that the coating is arranged regularly in the thickness direction, and the reflection path of radiation in different bands inside the coating is optimized, thereby obtaining excellent spectral control performance. The high-irradiation cooling window with graded metamaterial structure coating has extremely strong reflection characteristics greater than 0.96 in the ultraviolet-visible light-near infrared band of 0.25μm-2.5μm, and extremely strong emission characteristics greater than 0.95 in the mid-infrared band of 8μm-13μm. In addition, the graded metamaterial structure coating has excellent service performance. After testing, its adhesion is level 1; there are no wrinkles, cracks, or peeling after an impact of a 1kg hammer at a height of 50cm, and the paint film is not damaged after 5000 times of washing; there is no red rust on the surface after 200 hours of acetic acid salt spray; there is no abnormality after 168 hours of immersion in 5% sulfuric acid solution; there is no abnormality after 48 hours of immersion test in NaOH saturated solution; there is no bubble or crack after 1000W solar spectrum band irradiation (including 60W 300nm-400nm ultraviolet band irradiation) and 2000 hours of artificial climate aging, which meets the needs of long-term use of high-irradiation cooling windows in various scenarios.

[0064] 2. The high-radiation resistant cooling window with graded metamaterial structure coating of the present invention has extremely strong reflection characteristics in the ultraviolet-visible-near infrared band of 0.25-2.5μm, and extremely strong emission characteristics in the mid-infrared band of 8-13μm. Actual tests show that compared with ordinary windows, the indoor temperature of the room using the graded metamaterial structure high-radiation resistant coating cooling window is reduced by 8.05℃;

[0065] 3. The high-irradiation resistant cooling window with graded metamaterial structure coating of the present invention has excellent high-irradiation resistance and high-efficiency passive cooling characteristics. It can be suitable for building windows such as office buildings, factories, residential buildings, sentry boxes, mobile homes, glass curtain walls, exhibition halls and commercial centers, as well as transportation windows such as cars, trains, airplanes, ships and yachts, and special equipment windows such as space capsules, drones, armored vehicles, fighter jets and helicopters. The spectral control performance of the cooling window can be adaptively adjusted based on the indoor temperature, which significantly improves the indoor thermal comfort of buildings, transportation vehicles, special equipment sentry boxes, etc. under high solar radiation environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0067] Figure 1 It is a schematic diagram of the structure of the hierarchical metamaterial structure coating of the present invention applied on the surface of the shutter blade;

[0068] Figure 2 It is a schematic structural diagram of a high-irradiation resistant cooling window with a graded metamaterial structure coating according to one embodiment of the present invention;

[0069] Figure 3 It is a schematic structural diagram of a high-irradiation resistant cooling window with a graded metamaterial structure coating according to another embodiment of the present invention;

[0070] Figure 4 It is a schematic diagram of the principle of the high-irradiation-resistant cooling window with graded metamaterial structure coating of the present invention regulating the indoor ambient temperature in different temperature environments;

[0071] Figure 5 Comparison of the indoor temperature of a sentry booth using the cooling shutters of the present invention and a sentry booth using ordinary shutters;

[0072] Figure 6 1 is a cross-sectional SEM image of the coating with a graded metamaterial structure and the distribution of Ti elements in the interface direction in Example 17 of the present invention. DETAILED DESCRIPTION

[0073] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0074] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0075] In the embodiment section, the discussion focuses on cooling windows using transparent glass, with blinds as the main window form, and the blinds are made of aluminum. The manufacturing methods of cooling windows with other colors, transparencies, and coatings are similar to the following embodiments and all belong to the protection scope of the present invention.

[0076] The present application embodiment provides a high-irradiation resistant cooling window with a graded metamaterial structure coating, such as Figures 2-3 As shown, the high-radiation resistant cooling window comprises: a first glass, a second glass, a shutter and two window frames, the first glass and the second glass are arranged at intervals, and the shutter is located between the first glass and the second glass; the first glass, the second glass and the shutter are all fixed between the two window frames;

[0077] Or, the high-radiation resistant cooling window comprises: a first glass, a second glass, a shutter and two window frames, the first glass and the second glass are arranged at intervals, the shutter is located outside the second glass or the first glass, and the first glass, the second glass and the shutter are all fixed between the two window frames;

[0078] The surface of the shutter blades and window frames are equipped with high-irradiation resistant metamaterial coatings with graded metamaterial structures;

[0079] The high-irradiation resistant metamaterial coating includes: an optical functional layer with a microscopic hierarchical micro-nano structure;

[0080] The optical functional layer with microscopic hierarchical micro-nano structure comprises a first high molecular polymer and a first high refractive index inorganic spectral particle filler;

[0081] Inside the optical functional layer with a microscopic graded micro-nano structure, in its thickness direction, the size of the first high refractive index inorganic spectral particle filler is distributed from large to small or from small to large, and / or, in its thickness direction, the volume fraction of the first high refractive index inorganic spectral particle filler is distributed from large to small or from small to large.

[0082] Specific references Figure 2 As shown, the high-irradiation resistant cooling window structure includes: a first glass, a second glass and a shutter; and the first glass, the second glass and the shutter are all fixed on the window frame, the first glass, the second glass and the shutter are arranged in parallel and spaced apart, the shutter blades and the surface of the window frame are provided with a high-irradiation resistant metamaterial coating of a graded metamaterial structure, and the shutter is located between the first glass and the second glass. The first glass and the second glass can be transparent glass or light green tempered glass windows.

[0083] For further reference, Figure 3 As shown, the high-irradiation resistant cooling window structure includes: a first glass, a second glass and a shutter; and the first glass, the second glass and the shutter are all fixed on the window frame, the first glass, the second glass and the shutter are arranged in parallel and spaced apart, the shutter blades and the surface of the window frame are provided with a high-irradiation resistant metamaterial coating of a graded metamaterial structure, and the shutter is located outside the first glass or the second glass. The first glass and the second glass can be transparent glass or light green tempered glass windows.

[0084] The high-irradiation resistant cooling window with graded metamaterial structure coating of the present invention has a window frame and shutter blades made of steel, aluminum alloy, and plastic, and the outer surface thereof is coated with the graded metamaterial structure coating, and the amount of heat radiation entering the room can be controlled by adjusting the opening and closing angle of the shutter blades; the graded metamaterial structure coating is based on a polymer, and according to different functional requirements, a micro-nano structure is added to the polymer and coated on the window frame and the surface of the shutter blades, and the shutter is installed in the interlayer of the double-layer glass of the window or close to the surface of the external environment;

[0085] The graded metamaterial structure coating has a base layer, an optical functional layer with a micro-graded micro-nano structure, and a top hydrophobic protective layer. Based on different functional requirements, the material and micro-nano structure of each layer are designed in a targeted manner; in the optical function part, the size and volume fraction of the micro-nano structure are further used as the basis to arrange the optical functional layer in a graded manner in the thickness direction, and optimize the internal optical path, so that it has strong reflection characteristics in the 0.3-2.5μm solar spectrum band, and controls the thermal radiation input from the external environment; it has strong emission capabilities in the 8-13μm mid-infrared band and adjusts its own thermal radiation output.

[0086] The high-irradiation-resistant cooling window with graded metamaterial structure coating of the present invention has extremely high solar radiation reflection ability and mid-infrared emission ability, and can control the radiant heat entering the room by adjusting the opening and closing degree of the window, thereby achieving the effect of adjusting the indoor temperature;

[0087] The high-radiation-resistant cooling window with a graded metamaterial structure coating of the present invention can be applied to building windows such as office buildings, factories, residential buildings, sentry boxes, mobile homes, glass curtain walls, exhibition halls and commercial centers, as well as transportation windows such as cars, trains, airplanes, ships and yachts, and special equipment windows such as space capsules, drones, armored vehicles, fighter jets and helicopters. The material, size and grading method of the graded micro-nano structure used in the high-radiation-resistant cooling window are adjusted accordingly according to the transparency, color and other characteristics of the glass used in the window to achieve a better regulation effect.

[0088] Specifically, the graded metamaterial structure coating includes: an optical functional layer with a micro-graded micro-nano structure, the optical functional layer with a micro-graded micro-nano structure includes a first high molecular polymer and a first high refractive index inorganic spectral particle filler; the optical functional layer has a graded micro-nano structure, which is characterized in that: inside the optical functional layer with a micro-graded micro-nano structure, in its thickness direction, the size of the first high refractive index inorganic spectral particle filler follows a rule from large to small or from small to large, and / or, in its thickness direction, the volume fraction of the first high refractive index inorganic spectral particle filler follows a rule from large to small or from small to large (i.e. from sparse to dense or from dense to sparse) in the optical functional layer, this structure is different from the random distribution structure after simply mixing the matrix and the filler, and the micro-nano structure has an obvious regular spatial distribution; the graded and adjusted micro-nano structure can enable the window cooling component to obtain more excellent spectral performance to achieve the core functions of resisting high radiation and regulating indoor ambient temperature.

[0089] In some embodiments, the first high molecular polymer includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polychlorotrifluoroethylene, acrylic resin, epoxy resin, polyurethane, polyester resin, vinyl resin and silicone resin;

[0090] The first high-refractive inorganic spectral particulate filler comprises at least one of titanium dioxide, silicon dioxide, barium sulfate, aluminum oxide, zinc oxide, silicon carbide, zinc sulfide, boron nitride, magnesium oxide, barium carbonate and aluminum silicate;

[0091] The mass fraction of the first high-refractive inorganic spectral particle filler in the optical functional layer is 20 to 50%;

[0092] The particle size of the first high-refractive inorganic spectral particle filler is 10nm to 5000nm.

[0093] In some embodiments, the optical functional layer having the microscopic hierarchical micro-nano structure has a thickness of 50 μm to 200 μm.

[0094] In some embodiments, the metamaterial coating further includes a bottom layer, one surface of which is bonded to the surface of the window frame or the shutter blade, and the other surface is bonded to the optical functional layer with a microscopic hierarchical micro-nano structure, so as to improve the adhesion strength of the metamaterial coating; at the same time, it provides anti-corrosion properties and additional spectral performance for the overall coating; the bottom layer is between the window frame or the shutter blade and the spectrum regulation layer, and has strong adhesion properties, and its main function is to enhance the bonding strength between the spectrum regulation layer and the window frame or the shutter blade surface, and provide additional spectral functions. In some cases, the bottom layer is not a necessary structure of the metamaterial coating.

[0095] In some embodiments, the bottom layer comprises an organic second polymer and a functional filler; the bottom layer provides adhesion and anti-corrosion protection properties for the metamaterial coating as a whole;

[0096] The second high molecular polymer includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polychlorotrifluoroethylene, acrylic resin, epoxy resin, polyurethane, polyester resin, vinyl resin and silicone resin;

[0097] Functional fillers include the second highest refractive index inorganic spectral particles and anti-corrosion fillers;

[0098] The second high refractive inorganic spectral particulate filler includes at least one of titanium dioxide, silicon dioxide, barium sulfate, aluminum oxide, zinc oxide, silicon carbide, zinc sulfide, boron nitride, magnesium oxide, barium carbonate and aluminum silicate;

[0099] The anti-corrosion filler includes at least one of zinc powder, hexasodium phosphate, ferric oxide, zinc phosphate, and aluminum tripolyphosphate;

[0100] The mass fraction of functional filler in the bottom layer is 70-80%, among which the mass fraction of anti-corrosion filler in the bottom layer is 60-75%, and the rest is the second highest refractive index inorganic spectral particle filler; the particle size of anti-corrosion filler is 200nm-5000nm, and the particle size of the second highest refractive index inorganic spectral particles in the bottom layer is 10nm-5000nm.

[0101] The base material of the metamaterial coating is attached to the surface of the window frame or the shutter blade by spraying / scraping, and the coating thickness is 10μm to 100μm. The final finished coating appears to be a flat surface at the macro level, and its micro level shows that the anti-corrosion material and spectral material are randomly distributed inside.

[0102] In some embodiments, the metamaterial coating further includes a cover hydrophobic protective layer, which is located on the optical functional layer having a microscopic hierarchical micro-nano structure, is transparent or translucent, has strong adhesion properties, and provides hydrophobic protection properties for the coating. In addition, the cover hydrophobic protective layer portion can also be modulated to have additional spectral properties. In some cases of the present invention, the cover hydrophobic protective layer is not a necessary structure of the metamaterial coating.

[0103] The overlay hydrophobic protective layer includes a third high molecular weight polymer and a third high refractive inorganic spectral particle filler;

[0104] The third high molecular polymer includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polychlorotrifluoroethylene, acrylic resin, epoxy resin, polyurethane, polyester resin, vinyl resin and silicone resin; the coating has good hydrophobic properties by adding hydrophobic materials including at least one of silane coupling agent, silicone resin and nano silicon dioxide;

[0105] The third high refractive inorganic spectral particle filler includes at least one of titanium dioxide, silicon dioxide, barium sulfate, aluminum oxide, zinc oxide, silicon carbide, zinc sulfide, boron nitride, magnesium oxide, barium carbonate and aluminum silicate; its diameter is between 10nm-5000nm, and its mass fraction in the overcoat hydrophobic protective layer is between 5% and 10%. The overcoat hydrophobic protective layer material of the metamaterial coating is attached to the surface of the spectral regulation layer by spraying / scraping, and the coating thickness is 5μm-100μm.

[0106] In some embodiments, a diluent is used in the preparation of the bottom layer in the metamaterial coating, and the diluent is xylene;

[0107] The bottom layer includes a second high molecular polymer and xylene, wherein the second high molecular polymer includes a fluororesin and an acrylic resin, and the mass ratio of the fluororesin, the acrylic resin and the xylene is (15-20): (5-10): (25-35);

[0108] Or, the bottom layer includes a second high molecular polymer, an anti-corrosion filler, and xylene, the second high molecular polymer includes a fluororesin and an acrylic resin, the mass ratio of the fluororesin, the acrylic resin, the xylene, and the anti-corrosion filler is (15-20): (5-10): (25-40): (60-75); the anti-corrosion filler is zinc powder; the particle size of the anti-corrosion filler is 200nm-5000nm;

[0109] Or, the bottom layer includes a second high molecular polymer, an anti-corrosion filler, xylene, and a second high refractive index inorganic particle, the second high molecular polymer includes a fluororesin and an acrylic resin, and the mass ratio of the fluororesin, acrylic resin, xylene, the anti-corrosion filler, and the second high refractive index inorganic particle is (15-20): (5-10): (25-40): (60-75): (5-10); the second high refractive index inorganic particle is titanium dioxide, and the particle size of the second high refractive index inorganic particle is 100nm-500nm.

[0110] In some embodiments, a diluent is used in the preparation of the top hydrophobic protective layer in the metamaterial coating, and the diluent is xylene;

[0111] The overlay hydrophobic protective layer comprises a third high molecular weight polymer, a hydrophobic filler, and xylene, wherein the third high molecular weight polymer comprises a fluororesin and an acrylic resin, wherein the hydrophobic filler is a silane coupling agent, and the mass ratio of the fluororesin, the acrylic resin, the silane coupling agent, and the xylene is (55-65): (15-25): (70-80): (15-25);

[0112] Or, the cover hydrophobic protective layer includes a third high molecular weight organic polymer, xylene, and a third high refractive index inorganic spectral particle filler, wherein the third high molecular weight organic polymer includes fluororesin and acrylic resin, and the mass ratio of the fluororesin, acrylic resin, xylene, silane coupling agent, and the third high refractive index inorganic spectral particles is (55-65): (15-25): (70-80): (15-25): (5-15); the third high refractive index inorganic spectral particles are aluminum oxide with a diameter of 100nm to 300nm.

[0113] In some embodiments, the optical functional layer includes a plurality of mutually superimposed sub-optical functional layers, each optical functional layer includes a first high molecular polymer, a first high refractive index inorganic spectral particle, and xylene, and the first high molecular polymer includes a fluororesin and an acrylic resin;

[0114] The first high refractive index inorganic spectral particles include at least one of titanium dioxide with a particle size of 100nm to 500nm, titanium dioxide with a particle size of 500nm to 800nm, and titanium dioxide with a particle size of 800nm ​​to 1400nm;

[0115] The mass ratio of fluororesin, acrylic resin, xylene and the first high refractive index inorganic spectral particles is (55-65): (15-25): (60-70): (20-80).

[0116] In some embodiments, the optical functional layer having a microscopic hierarchical micro-nano structure is composed of two sub-optical functional layers including a bottom optical functional layer and an upper optical functional layer from bottom to top;

[0117] The first high refractive index inorganic spectral particles in the upper optical functional layer are titanium dioxide with a particle size of 100nm to 500nm;

[0118] The first high refractive index inorganic spectral particle in the bottom optical functional layer is titanium dioxide with a particle size of 500nm to 800nm;

[0119] In some embodiments, the optical functional layer with microscopic hierarchical micro-nano structure includes three sub-optical functional layers from bottom to top: an upper optical functional layer, a middle optical functional layer, and a bottom optical functional layer;

[0120] The first high refractive index inorganic spectral particles in the upper optical functional layer are titanium dioxide with a particle size of 100nm to 500nm;

[0121] The first high refractive index inorganic spectral particle in the middle optical functional layer is titanium dioxide with a particle size of 500nm to 800nm;

[0122] The first high-refractive-index inorganic spectral particles in the bottom optical functional layer are titanium dioxide with a particle size of 800nm ​​to 1400nm.

[0123] In some embodiments, the first high refractive index inorganic spectral particles in the optical functional layer having a micro-graded micro-nano structure include a mixture of titanium dioxide with a mass ratio of (3-7): (1-3): (1-3) with particle sizes of 100nm-500nm, 500nm-800nm, and 800nm-1400nm respectively.

[0124] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned high-irradiation resistant cooling window with a graded metamaterial structure coating, comprising:

[0125] A high-irradiation resistant metamaterial coating is prepared on the surface of a window frame or a shutter blade, wherein the high-irradiation resistant metamaterial coating includes an optical functional layer with a hierarchical micro-nano structure, and a method for preparing the optical functional layer with a microscopic hierarchical micro-nano structure includes:

[0126] Adding a first high refractive index inorganic spectral particle filler and an optional diluent into a first high molecular polymer, stirring and mixing, to obtain a spectral functional mixture;

[0127] The spectral functional mixture is coated on the surface of the window frame or the shutter blade to form a light functional layer with a microscopic hierarchical micro-nano structure, thereby obtaining a hierarchical metamaterial structure coating;

[0128] Alternatively, the high-irradiation resistant metamaterial coating comprises a bottom layer and an optical functional layer having a microscopic hierarchical micro-nano structure, and the preparation method of the high-irradiation resistant metamaterial coating comprises the following steps:

[0129] Adding optional second high refractive index inorganic spectral particles, optional anti-corrosion filler, and optional diluent to the second high molecular polymer, stirring and mixing, to obtain a bottom layer mixture;

[0130] Apply the primer mixture to the surface of the window frame or shutter blades to form a primer;

[0131] Adding a first high refractive index inorganic spectral particle filler and an optional diluent into a first high molecular polymer, stirring and mixing, to obtain a spectral functional mixture;

[0132] The spectral functional mixture is coated on the surface of the bottom layer to form a light functional layer with a microscopic hierarchical micro-nano structure;

[0133] Alternatively, the high-irradiation resistant metamaterial coating comprises a bottom layer, an optical functional layer having a microscopic hierarchical micro-nano structure, and a cover hydrophobic protective layer. The preparation method of the high-irradiation resistant metamaterial coating comprises the following steps:

[0134] Adding optional second high refractive index inorganic spectral particles, optional anti-corrosion filler, and optional diluent to the second high molecular polymer, stirring and mixing, to obtain a bottom layer mixture;

[0135] Apply the primer mixture to the surface of the window frame or shutter blades to form a primer;

[0136] Adding a first high refractive index inorganic spectral particle filler with different physical properties and an optional diluent into a first high molecular polymer, stirring and mixing, to obtain a plurality of spectral functional mixtures;

[0137] Applying a plurality of spectral functional mixtures in sequence on the surface of the bottom layer to form a light functional layer with a microscopic hierarchical micro-nano structure;

[0138] Adding the optional third high-refractive inorganic spectral particles, hydrophobic material, and optional diluent to the third high molecular weight polymer, stirring and mixing, to obtain a surface hydrophobic protective layer mixture;

[0139] The surface hydrophobic protective layer mixture is coated on the surface of the optical functional layer having a microscopic hierarchical micro-nano structure to form a surface hydrophobic protective layer;

[0140] The first glass, the second glass, and the shutters formed with the high-radiation resistant metamaterial coating are all installed between the window outer frame formed with the high-radiation resistant metamaterial coating, so as to obtain the high-radiation resistant cooling window with the high-radiation resistant coating of the graded metamaterial structure.

[0141] Specific references Figure 1 As shown, a hierarchical metamaterial structure coating is prepared on the surface of the blinds blades. Specifically, a bottom layer, an optical functional layer, and a cover hydrophobic protective layer are prepared in sequence on the surface of the blinds blades; further, from Figure 1 From the local enlarged view of the medium optical functional layer, it can be seen that inside the optical functional layer, in the thickness direction, the size of the first high refractive index inorganic spectral particle filler is distributed from large to small or from small to large; in the thickness direction, the volume fraction of the first high refractive index inorganic spectral particle filler is distributed from large to small or from small to large (i.e., from sparse to dense or from dense to sparse).

[0142] For further reference, Figure 4 As shown, it shows a schematic diagram of the surface of the blinds and the indoor temperature under different irradiation environments after the hierarchical metamaterial structure coating of the present invention is prepared on the blinds. Under strong solar irradiation, the blinds are closed or the opening and closing angles of the blinds are reduced. The blinds with the metamaterial coating of the present invention can reflect sunlight and thus adjust the indoor temperature; under weak solar irradiation, the blinds are opened to adjust the indoor temperature.

[0143] The metamaterial coating of the present invention can improve the radiation resistance of window building materials, including improving the reflective properties of the carrier surface for the solar radiation band and improving the radiation properties of the carrier in the mid-infrared band. The metamaterial coating of the present invention is combined with the carrier in a manner including but not limited to spraying, brushing, roller coating, electrostatic spraying, pasting, laminating, hot pressing and other surface combination methods or chemical fusion methods. The macroscopic morphology of the metamaterial coating of the present invention is a periodic or pseudo-periodic morphology in various forms such as layered plane, curved surface, roughening, sand wall and the like.

[0144] The metamaterial coating provided by the present invention has organic polymers and inorganic spectral particles as main components, and realizes the function of regulating the reflectivity and emissivity of the solar spectrum (0.3-2.5μm) and the mid-infrared spectrum (8-13μm) by constructing a structure with integrated macrostructure and hierarchical microstructure.

[0145] Based on the same inventive concept, the present invention also provides an anti-high-radiation cooling window with a graded metamaterial structure coating or the obtained high-radiation cooling window with a graded metamaterial structure coating prepared by the preparation method thereof, which can be used in scenes such as office buildings, factory buildings, residential buildings, sentry boxes, mobile homes, glass curtain walls, exhibition halls and commercial centers, as well as in windows of transportation vehicles such as cars, trains, airplanes, ships and yachts, and in windows of special equipment such as space capsules, drones, armored vehicles, fighter jets and helicopters.

[0146] The high-irradiation resistant cooling window with a graded metamaterial structure coating of the present invention has excellent high-irradiation resistance and high-efficiency passive cooling characteristics. It can be suitable for building windows such as office buildings, factories, residential buildings, sentry boxes, mobile homes, glass curtain walls, exhibition halls and commercial centers, as well as transportation windows such as cars, trains, airplanes, ships and yachts, and special equipment windows such as space capsules, drones, armored vehicles, fighter jets and helicopters. The spectral control performance of the cooling window can be adaptively adjusted based on the indoor temperature, which significantly improves the indoor thermal comfort of buildings, transportation vehicles, special equipment, etc. under high solar radiation environments.

[0147] The following further illustrates the metamaterial coating and its preparation method of the present application with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0148] The metamaterial coating structure of this embodiment includes a bottom layer, an optical functional layer and a protective cover hydrophobic protective layer. The optical functional layer is a required layer, and the bottom layer and the cover hydrophobic protective layer are optional layers, which can be added or subtracted according to the specific carrier material. The following will explain the structure of each layer of the metamaterial coating through a scheme, and finally further explain the specific metamaterial coating through an embodiment. Unless otherwise specified, the production formula is a weight ratio unless otherwise specified. The combination method between the layers is spraying, and the curing method is one or more of natural drying and high-temperature baking.

[0149] The embodiments of the present invention all use blinds as the main form of windows, and other windows with opening and closing mechanisms and covering capabilities are all within the scope of patent protection.

[0150] In the embodiment of the present invention, unless otherwise specified, it is assumed that the coating base layer is coated on the surface of the blind blades, the light functional layer is coated on the surface of the base layer, and the top hydrophobic protective layer is coated on the surface of the light functional layer.

[0151] Unless otherwise specified, the embodiments of the present invention have all used the currently widely used double-glazed windows as the experimental scene.

[0152] The reflectivity listed in this embodiment refers to the proportion of the reflection on the surface of the shutter blade to the proportion of the radiation energy incident on the surface of the shutter blade.

[0153] The polymer carrier used in the embodiment of the present invention is PVDF fluororesin, which needs to be baked at high temperature during the film forming process; other types of fluororesins, acrylic acid, epoxy resin and other polymer materials do not need to be baked at high temperature during the film forming process, but the preparation process is similar to that of this patent and should also be within the scope of protection of this patent.

[0154] In the following examples, PVDF fluororesin and acrylic resin are used, wherein the PVDF fluororesin is a PVDF emulsion from Dongguan Suyu Plastic Technology Co., Ltd.; and the acrylic resin is an acrylic emulsion provided by Henan Dazao Chemical Industry.

[0155] Example 1

[0156] This embodiment provides a method for preparing a bottom layer, including Scheme 1, Scheme 2, and Scheme 3.

[0157] Solution 1

[0158] This solution provides a method for preparing a bottom layer, comprising the following steps:

[0159] S1, 50g PVDF fluorine resin and 25g acrylic resin were mixed and stirred for 15min to obtain a matrix material;

[0160] S2, mix the base material in S1 with 75g of xylene and stir for 10min to obtain a bottom layer mixture;

[0161] S3. Spray the bottom layer mixture in S2 onto the surface of the shutter blades to form a coating structure with a flat appearance and a dense internal microstructure. Let it stand for 10 minutes, bake at 230°C for 20 minutes, and obtain the bottom layer after curing. The bottom layer thickness is 10 μm.

[0162] Solution 2

[0163] This solution provides a method for preparing a bottom layer, comprising the following steps:

[0164] S1, 50g of fluororesin and 25g of acrylic resin were mixed and stirred for 15min to obtain a matrix material;

[0165] S2, mixing the base material in S1 with 75 g of xylene, and stirring for 10 min to obtain a diluted base material;

[0166] S3, adding 130 g of zinc powder with a particle size of 5 μm as an anti-corrosion material to the base material diluted in S2, stirring for 20 minutes to obtain a bottom layer mixture;

[0167] S4. Spray the bottom layer mixture in S3 onto the surface of the shutter blades to form a coating structure with a flat appearance and a dense internal microstructure. Let it stand for 10 minutes, bake at 230°C for 20 minutes, and obtain the bottom layer after curing. The bottom layer thickness is 10 μm.

[0168] Solution 3

[0169] This solution provides a method for preparing a bottom layer, comprising the following steps:

[0170] S1, 50g of fluororesin and 25g of acrylic resin were mixed and stirred for 15min to obtain a matrix material;

[0171] S2, mixing the base material in S1 with 75 g of xylene, and stirring for 10 min to obtain a diluted base material;

[0172] S3, adding 130 g of zinc powder with a particle size of 5 μm as an anti-corrosion material to the base material diluted in S2, stirring for 20 minutes, to obtain an intermediate bottom material;

[0173] S4, adding 15 g of titanium dioxide with a particle size of 400 nm to the intermediate bottom layer material in S3, stirring for 20 min to obtain a bottom layer mixture;

[0174] S5. Spray the bottom layer mixture in S4 onto the surface of the shutter blades to form a coating structure with a flat appearance and a dense internal microstructure. Let it stand for 10 minutes, bake at 230°C for 20 minutes, and obtain the bottom layer after curing. The bottom layer thickness is 10 μm.

[0175] Example 2

[0176] This embodiment provides a method for preparing a photofunctional layer having a microscopic hierarchical micro-nano structure, including Scheme 1, Scheme 2, Scheme 3, Scheme 4, Scheme 5, and Scheme 6.

[0177] Solution 1

[0178] This solution provides a method for preparing a photofunctional layer having a microscopic hierarchical micro-nano structure, comprising the following steps:

[0179] S1, 50g of fluororesin and 25g of acrylic resin were mixed and stirred for 15min to obtain a matrix material;

[0180] S2, mixing the base material in S1 with 75 g of xylene, and stirring for 10 min to obtain a diluted base material;

[0181] S3, adding 50 g of titanium dioxide with a particle size of 400 nm to the base material diluted in S2, stirring for 25 minutes, to obtain a light function layer mixture;

[0182] S4. Spray the light functional layer mixture in S3 onto the surface of the bottom layer, let it stand for 15 minutes, bake it at 230° C. for 20 minutes, and obtain the light functional layer after curing. The thickness of the light functional layer is 150 μm.

[0183] Solution 2

[0184] This solution provides a method for preparing a photofunctional layer having a microscopic hierarchical micro-nano structure, comprising the following steps:

[0185] S1, 50g of fluororesin and 25g of acrylic resin were mixed and stirred for 15min to obtain a matrix material;

[0186] S2, mixing the base material in S1 with 25 g of xylene, stirring for 10 min to obtain a diluted base material;

[0187] S3, preparing two portions of diluted matrix material according to the method in S2;

[0188] S4, adding 50 g of titanium dioxide with a particle size of 400 nm to the first diluted base material, stirring for 25 min, to obtain an upper optical functional layer mixture;

[0189] S5, adding 50 g of titanium dioxide with a particle size of 800 nm to the diluted base material of the bottom layer, stirring for 25 min, to obtain a bottom optical functional layer mixture;

[0190] S6. Spray the bottom optical functional layer mixture in S4 onto the surface of the bottom layer, let it stand for 15 minutes, bake at 230°C for 20 minutes, and obtain the first optical functional layer after curing; spray the upper optical functional layer mixture in S5 onto the surface of the bottom optical functional layer, let it stand for 15 minutes, bake at 230°C for 20 minutes, and obtain the bottom optical functional layer after curing; the thickness of the upper functional layer and the bottom optical functional layer are both 75μm; the upper optical functional layer and the bottom optical functional layer are overlapped to form an entire optical functional layer with a microscopic hierarchical micro-nano structure.

[0191] The optical functional layer with microscopic hierarchical micro-nano structure prepared in this scheme has a hierarchical structure, which is manifested in that the particle diameters are divided into two levels from small to large along the thickness direction of the film layer.

[0192] Solution 3

[0193] This solution provides a method for preparing a photofunctional layer having a microscopic hierarchical micro-nano structure, comprising the following steps:

[0194] S1, 50g of fluororesin and 25g of acrylic resin were mixed and stirred for 15min to obtain a matrix material;

[0195] S2, mixing the base material in S1 with 75 g of xylene, and stirring for 10 min to obtain a diluted base material;

[0196] S3, preparing three diluted base materials according to the method in S2;

[0197] S4, adding 50 g of titanium dioxide with a particle size of 400 nm to the first diluted base material, stirring for 25 min, to obtain an upper optical functional layer mixture;

[0198] S5, adding 50 g of titanium dioxide with a particle size of 800 nm to the second diluted base material, stirring for 25 min, to obtain a middle-layer optical functional layer mixture;

[0199] S6, adding 50 g of titanium dioxide with a particle size of 1000 nm to the third diluted base material, stirring for 25 minutes, to obtain a bottom optical functional layer mixture;

[0200] S7. Spray the bottom optical functional layer mixture in S4 on the surface of the bottom layer, let it stand for 15 minutes, bake at 230°C for 20 minutes, and solidify; spray the middle optical functional layer mixture in S5 on the surface of the bottom optical functional layer, let it stand for 15 minutes, bake at 230°C for 20 minutes, and solidify; spray the upper optical functional layer mixture in S6 on the surface of the middle optical functional layer, let it stand for 15 minutes, bake at 230°C for 20 minutes, and solidify; the thickness of the upper optical functional layer, the middle optical functional layer, and the bottom optical functional layer are all 50μm; the upper optical functional layer, the middle optical functional layer, and the bottom optical functional layer are overlapped to form an entire optical functional layer with a microscopic hierarchical micro-nano structure.

[0201] The optical functional layer prepared in this scheme has a graded structure, which is manifested in that the particle diameters are divided into three levels from small to large along the thickness direction of the film layer.

[0202] Solution 4

[0203] This solution provides a method for preparing a photofunctional layer having a microscopic hierarchical micro-nano structure, comprising the following steps:

[0204] S1, 50g of fluororesin and 25g of acrylic resin were mixed and stirred for 15min to obtain a matrix material;

[0205] S2, mixing the base material in S1 with 75 g of xylene, and stirring for 10 min to obtain a diluted base material;

[0206] S3, preparing two portions of diluted matrix material according to the method in S2;

[0207] S4, adding 50 g of titanium dioxide with a particle size of 400 nm to the first diluted base material, stirring for 25 minutes, to obtain a bottom optical functional layer mixture;

[0208] S5, adding 25 g of titanium dioxide with a particle size of 800 nm to the second diluted base material, stirring for 25 min, to obtain an upper optical functional layer mixture;

[0209] S6. Spray the bottom optical functional layer mixture in S4 on the surface of the bottom layer, let it stand for 15 minutes, bake at 230°C for 20 minutes, and solidify; spray the upper optical functional layer mixture in S5 on the surface of the bottom optical functional layer, let it stand for 15 minutes, bake at 230°C for 20 minutes, and obtain the second optical functional layer after solidification; the thickness of the first optical functional layer and the second optical functional layer are both 75μm; the upper optical functional layer and the bottom functional layer are overlapped to form an entire optical functional layer with a microscopic hierarchical micro-nano structure.

[0210] The optical functional layer prepared in this scheme has a graded structure, which is manifested in that the particle diameter is divided into two levels from small to large along the film thickness direction, and the particle volume fraction is divided into two levels from large to small.

[0211] Solution 5

[0212] This solution provides a method for preparing a photofunctional layer having a microscopic hierarchical micro-nano structure, comprising the following steps:

[0213] S1, 50g of fluororesin and 25g of acrylic resin were mixed and stirred for 15min to obtain a matrix material;

[0214] S2, mixing the base material in S1 with 75 g of xylene, and stirring for 10 min to obtain a diluted base material;

[0215] S3, preparing three diluted base materials according to the method in S2;

[0216] S4, adding 50 g of titanium dioxide with a particle size of 400 nm to the first diluted base material, stirring for 25 min, to obtain an upper optical functional layer mixture;

[0217] S5, adding 25 g of titanium dioxide with a particle size of 800 nm to the second diluted base material, stirring for 25 min, to obtain a middle-layer optical functional layer mixture;

[0218] S6, adding 15 g of titanium dioxide with a particle size of 1000 nm to the third diluted base material, stirring for 25 minutes, to obtain a bottom optical functional layer mixture;

[0219] S7. Spray the bottom optical functional layer mixture in S4 on the surface of the bottom layer, let it stand for 15 minutes, bake at 230°C for 20 minutes, and solidify; spray the middle optical functional layer mixture in S5 on the surface of the bottom optical functional layer, let it stand for 15 minutes, bake at 230°C for 20 minutes, and solidify; spray the upper optical functional layer mixture in S6 on the surface of the middle optical functional layer, let it stand for 15 minutes, bake at 230°C for 20 minutes, and solidify; the thickness of the upper functional layer, the middle optical functional layer, and the bottom optical functional layer are all 50μm, which are superimposed to form an entire optical functional layer with a microscopic hierarchical micro-nano structure.

[0220] The optical functional layer prepared in this scheme has a graded structure, which is manifested in that the particle diameter is divided into three levels from small to large along the film thickness direction, and the particle volume fraction is divided into three levels from large to small.

[0221] Solution 6

[0222] This solution provides a method for preparing a photofunctional layer having a microscopic hierarchical micro-nano structure, comprising the following steps:

[0223] S1, 50g of fluororesin and 25g of acrylic resin were mixed and stirred for 15min to obtain a matrix material;

[0224] S2, mixing the base material in S1 with 150 g of xylene, stirring for 10 min, to obtain a diluted base material;

[0225] S3, titanium dioxide with a particle size of 400 nm, titanium dioxide with a particle size of 800 nm, and titanium dioxide with a particle size of 1000 nm are mixed in a mass ratio of 5:2:1 to obtain titanium dioxide mixed particles;

[0226] S4, adding 50 g of the titanium dioxide mixed particles in step S3 to the base material diluted in S2, stirring for 25 minutes, to obtain a light function layer mixture;

[0227] S5. Spray the photofunctional layer mixture in S4 onto the surface of the base layer, let it stand for 20 minutes, bake at 230°C for 20 minutes, and obtain a photofunctional layer with a micro-graded micro-nano structure after curing. The thickness of the photofunctional layer is 150μm. During the curing process of the coating, as the internal particles gradually settle under the action of gravity, a distribution state of gradual transition from small particle size to large particle size is formed in the direction of the coating thickness from the surface layer to the bottom layer.

[0228] The optical functional layer prepared in this scheme has a graded structure, which is manifested in that the particle diameter is gradually distributed from small to large along the thickness direction of the film layer.

[0229] Example 3

[0230] This embodiment provides a method for preparing a hydrophobic protective layer on a cover surface, including Scheme 1, Scheme 2, and Scheme 3.

[0231] Solution 1

[0232] This solution provides a method for preparing a hydrophobic protective layer on a surface, comprising the following steps:

[0233] S1, 50g of fluororesin and 25g of acrylic resin were mixed and stirred for 15min to obtain a matrix material;

[0234] S2, mixing the base material in S1 with 75g of xylene, stirring for 10min, to obtain a surface hydrophobic protective layer mixture;

[0235] S3, spraying the mixture of the top hydrophobic protective layer in S2 on the surface of the light functional layer, baking at 230° C. for 20 minutes, and obtaining the top hydrophobic protective layer after curing; the thickness of the top hydrophobic protective layer is 20 μm.

[0236] Solution 2

[0237] This solution provides a method for preparing a hydrophobic protective layer on a surface, comprising the following steps:

[0238] S1, 50g of fluororesin and 25g of acrylic resin were mixed and stirred for 15min to obtain a matrix material;

[0239] S2, mixing the base material in S1 with 75 g of xylene, and stirring for 10 min to obtain a diluted base material;

[0240] S3, adding 20 g of aluminum oxide with a particle size of 500 nm to the base material diluted in S2, stirring for 25 minutes, to obtain a surface hydrophobic protective layer mixture;

[0241] S4, spray the mixture of the top hydrophobic protective layer in S3 on the surface of the light functional layer, let it stand for 20 minutes, and then bake it at 230° C. for 20 minutes, and obtain the top hydrophobic protective layer after curing; the thickness of the top hydrophobic protective layer is 20 μm.

[0242] Solution 3

[0243] This solution provides a method for preparing a hydrophobic protective layer on a cover surface, comprising the following steps:

[0244] S1, 50g of fluororesin and 25g of acrylic resin were mixed and stirred for 15min to obtain a matrix material;

[0245] S2, mixing the base material in S1 with 75 g of xylene, and stirring for 10 min to obtain a diluted base material;

[0246] S3, adding 20 g of aluminum oxide with a particle size of 500 nm to the base material diluted in S2, stirring for 25 minutes, to obtain an intermediate state mixture of a hydrophobic protective layer;

[0247] S4, adding 15 g of hydrophobic nano-silicon oxide with a particle size of 20 nm to the base material diluted in S3, stirring for 25 min, to obtain a surface hydrophobic protective layer mixture;

[0248] S4, spraying the mixture of the top hydrophobic protective layer in S3 on the surface of the optical functional layer, leaving it to stand for 20 minutes and then baking it at 230° C. for 20 minutes, and obtaining the top hydrophobic protective layer after curing; the thickness of the top hydrophobic protective layer is 20 μm;

[0249] Example 4

[0250] This embodiment provides a graded metamaterial structure coating, which only includes an optical functional layer. According to the method of Scheme 3 in Example 2, the optical functional layer mixture is sprayed on the surface of the carrier material and baked at 230° C. for 20 minutes to form the optical functional layer.

[0251] Example 5

[0252] This embodiment provides a graded metamaterial structure coating, which only includes an optical functional layer. According to the method of Scheme 5 in Example 2, the optical functional layer mixture is sprayed on the surface of the blinds blades and baked at 230° C. for 20 minutes to form the optical functional layer.

[0253] Example 6

[0254] This embodiment provides a graded metamaterial structure coating, which only includes an optical functional layer. According to the method of Scheme 6 in Example 2, the optical functional layer mixture is sprayed on the surface of the shutter blades and baked at 230° C. for 20 minutes to form the optical functional layer.

[0255] Example 7

[0256] The present embodiment provides a graded metamaterial structure coating, including a bottom layer and an optical functional layer. The bottom layer mixture is sprayed on the surface of the blind blade according to the method of Scheme 1 in Example 1, and allowed to stand for 20 minutes to form a bottom layer; then the optical functional layer mixture is sprayed on the surface of the bottom layer according to the method of Scheme 3 in Example 2, and baked at 230°C for 20 minutes to form a optical functional layer.

[0257] Example 8

[0258] The present embodiment provides a graded metamaterial structure coating, including a bottom layer and an optical functional layer. The bottom layer mixture is sprayed on the surface of the shutter blade according to the method of Scheme 1 in Example 1, and allowed to stand for 20 minutes to form a bottom layer; then the optical functional layer mixture is sprayed on the surface of the bottom layer according to the method of Scheme 5 in Example 2, and baked at 230°C for 20 minutes to form a optical functional layer.

[0259] Example 9

[0260] The present embodiment provides a graded metamaterial structure coating, including a base layer and an optical functional layer. The base layer is sprayed with a base layer mixture on the surface of a carrier material (specifically, an aluminum blind) according to the method of Scheme 1 in Example 1, allowed to stand for 20 minutes, baked at 230°C for 20 minutes, and solidified to form a base layer; then, the optical functional layer mixture is sprayed on the surface of the base layer according to the method of Scheme 6 in Example 2, and baked at 230°C for 20 minutes to form a optical functional layer.

[0261] Example 10

[0262] The present embodiment provides a graded metamaterial structure coating, including a base layer and an optical functional layer. The base layer is sprayed with a base layer mixture on the surface of a venetian blind blade according to the method of Scheme 3 in Example 1, left to stand for 20 minutes, baked at 230°C for 20 minutes, and solidified to form a base layer; then, the optical functional layer mixture is sprayed on the surface of the base layer according to the method of Scheme 3 in Example 2, and baked at 230°C for 20 minutes to form a optical functional layer.

[0263] Embodiment 11

[0264] The present embodiment provides a graded metamaterial structure coating, including a base layer and an optical functional layer. The base layer is sprayed with a base layer mixture on the surface of a venetian blind blade according to the method of Scheme 3 in Example 1, left to stand for 20 minutes, baked at 230°C for 20 minutes, and solidified to form a base layer; then, the optical functional layer mixture is sprayed on the surface of the base layer according to the method of Scheme 5 in Example 2, and baked at 230°C for 20 minutes to form a optical functional layer.

[0265] Example 12

[0266] The present embodiment provides a graded metamaterial structure coating, including a base layer and an optical functional layer. The base layer mixture is sprayed on the surface of the shutter blade according to the method of Scheme 3 in Example 1, left to stand for 20 minutes, baked at 230°C for 20 minutes, and solidified to form a base layer; then the optical functional layer mixture is sprayed on the surface of the base layer according to the method of Scheme 6 in Example 2, and baked at 230°C for 20 minutes to form the optical functional layer.

[0267] Embodiment 13

[0268] The present embodiment provides a graded metamaterial structure coating, including a base layer, an optical functional layer, and a top hydrophobic protective layer. The base layer is sprayed on the surface of the blind blade according to the method of Scheme 3 in Example 1, allowed to stand for 15 minutes, baked at 230°C for 20 minutes, and solidified to form a base layer; then, according to the method of Scheme 3 in Example 2, the optical functional layer mixture is sprayed on the surface of the base layer, allowed to stand for 15 minutes, baked at 230°C for 20 minutes, and solidified to form a optical functional layer; then, according to the method of Scheme 1 in Example 3, the top hydrophobic protective layer mixture is sprayed on the surface of the optical functional layer, allowed to stand for 20 minutes, and baked at 230°C for 20 minutes to form a top hydrophobic protective layer.

[0269] Embodiment 14

[0270] The present embodiment provides a graded metamaterial structure coating, including a base layer, an optical functional layer, and a top hydrophobic protective layer. The base layer is sprayed on the surface of the blind blade according to the method of Scheme 3 in Example 1, allowed to stand for 15 minutes, baked at 230°C for 20 minutes, and solidified to form a base layer; then, according to the method of Scheme 5 in Example 2, the optical functional layer mixture is sprayed on the surface of the base layer, allowed to stand for 15 minutes, baked at 230°C for 20 minutes, and solidified to form a optical functional layer; then, according to the method of Scheme 1 in Example 3, the top hydrophobic protective layer mixture is sprayed on the surface of the optical functional layer, allowed to stand for 20 minutes, and baked at 230°C for 20 minutes to form a top hydrophobic protective layer.

[0271] Embodiment 15

[0272] The present embodiment provides a graded metamaterial structure coating, including a base layer, an optical functional layer, and a top hydrophobic protective layer. The base layer is sprayed on the surface of the blind blade according to the method of Scheme 3 in Example 1, allowed to stand for 15 minutes, baked at 230°C for 20 minutes, and solidified to form a base layer; then, according to the method of Scheme 6 in Example 2, the optical functional layer mixture is sprayed on the surface of the base layer, allowed to stand for 15 minutes, baked at 230°C for 20 minutes, and solidified to form a optical functional layer; then, according to the method of Scheme 1 in Example 3, the top hydrophobic protective layer mixture is sprayed on the surface of the optical functional layer, allowed to stand for 20 minutes, and baked at 230°C for 20 minutes to form a top hydrophobic protective layer.

[0273] Example 16

[0274] The present embodiment provides a graded metamaterial structure coating, including a base layer, an optical functional layer, and a top hydrophobic protective layer. The base layer is sprayed on the surface of the blind blade according to the method of Scheme 3 in Example 1, allowed to stand for 15 minutes, baked at 230°C for 20 minutes, and solidified to form a base layer; then, according to the method of Scheme 3 in Example 2, the optical functional layer mixture is sprayed on the surface of the base layer, allowed to stand for 15 minutes, baked at 230°C for 20 minutes, and solidified to form a optical functional layer; then, according to the method of Scheme 3 in Example 3, the top hydrophobic protective layer mixture is sprayed on the surface of the optical functional layer, allowed to stand for 20 minutes, and baked at 230°C for 20 minutes, to form a top hydrophobic protective layer.

[0275] Embodiment 17

[0276] The present embodiment provides a graded metamaterial structure coating, including a base layer, an optical functional layer, and a top hydrophobic protective layer. The base layer is sprayed on the surface of the blind blade according to the method of Scheme 3 in Example 1, allowed to stand for 15 minutes, baked at 230°C for 20 minutes, and solidified to form a base layer; then, according to the method of Scheme 5 in Example 2, the optical functional layer mixture is sprayed on the surface of the base layer, allowed to stand for 15 minutes, baked at 230°C for 20 minutes, and solidified to form a optical functional layer; then, according to the method of Scheme 3 in Example 3, the top hydrophobic protective layer mixture is sprayed on the surface of the optical functional layer, allowed to stand for 20 minutes, and baked at 230°C for 20 minutes to form a top hydrophobic protective layer.

[0277] Embodiment 18

[0278] The present embodiment provides a graded metamaterial structure coating, including a base layer, an optical functional layer, and a top hydrophobic protective layer. The base layer is sprayed on the surface of the blind blade according to the method of Scheme 3 in Example 1, allowed to stand for 15 minutes, baked at 230°C for 20 minutes, and solidified to form a base layer; then, according to the method of Scheme 6 in Example 2, the optical functional layer mixture is sprayed on the surface of the base layer, allowed to stand for 15 minutes, baked at 230°C for 20 minutes, and solidified to form a optical functional layer; then, according to the method of Scheme 3 in Example 3, the top hydrophobic protective layer mixture is sprayed on the surface of the optical functional layer, allowed to stand for 20 minutes, and baked at 230°C for 20 minutes to form a top hydrophobic protective layer.

[0279] Embodiment 19

[0280] This embodiment provides a graded metamaterial structure coating, including a base layer, a light functional layer, and a top hydrophobic protective layer. The construction process is exactly the same as that of Example 17, except that the blinds prepared in this embodiment are installed in a window interlayer with light green glass.

[0281] Embodiment 20

[0282] This embodiment provides a graded metamaterial structure coating, including a base layer, a light functional layer, and a top hydrophobic protective layer. The construction process is exactly the same as that of Example 17, except that the blinds prepared in this embodiment are installed on the outermost surface of the window close to the outdoors.

[0283] Comparative Example 1

[0284] This comparison example provides aluminum shutters that only include the original factory protective coating without any additional surface treatment.

[0285] Comparative Example 2

[0286] This comparison provides aluminum shutters that only include the original protective coating, which is only painted with acrylic resin and forms an additional protective layer.

[0287] Comparative Example 3

[0288] This comparative example provides a commonly used spectral regulation coating form, which only includes a light functional layer, and the spectral functional layer does not have a graded structure. According to the method of Scheme 1 in Example 2, the light functional layer mixture is sprayed on the surface of the blinds blades, left to stand for 20 minutes and baked at 230°C for 20 minutes to form a light functional layer.

[0289] Comparative Example 4

[0290] This comparative example provides a graded metamaterial structure coating, which only includes an optical functional layer. According to the method of Scheme 2 in Example 2, the optical functional layer mixture is sprayed on the surface of the blinds blades, left to stand for 20 minutes and baked at 230° C. for 20 minutes to form the optical functional layer.

[0291] Comparative Example 5

[0292] This comparative example provides a graded metamaterial structure coating, which only includes an optical functional layer. According to the method of Scheme 4 in Example 2, the optical functional layer mixture is sprayed on the surface of the blinds blades, left to stand for 20 minutes and baked at 230° C. for 20 minutes to form the optical functional layer.

[0293] Comparative Example 6

[0294] The present comparative example provides a graded metamaterial structure coating, including a base layer and an optical functional layer. The base layer is sprayed with a base layer mixture on the surface of a venetian blind blade according to the method of Scheme 1 in Example 1, allowed to stand for 20 minutes, baked at 230°C for 20 minutes, and solidified to form a base layer; and then the optical functional layer mixture is sprayed on the surface of the base layer according to the method of Scheme 1 in Example 2, allowed to stand for 20 minutes, and baked at 230°C for 20 minutes to form an optical functional layer.

[0295] Comparative Example 7

[0296] The present comparative example provides a graded metamaterial structure coating, including a base layer and an optical functional layer. The base layer mixture is sprayed on the surface of the blind blade according to the method of Scheme 3 in Example 1, allowed to stand for 20 minutes, baked at 230°C for 20 minutes, and solidified to form a base layer; then the optical functional layer mixture is sprayed on the surface of the base layer according to the method of Scheme 1 in Example 2, allowed to stand for 20 minutes, and baked at 230°C for 20 minutes to form a optical functional layer.

[0297] Comparative Example 8

[0298] The present comparative example provides a graded metamaterial structure coating, including a base layer, an optical functional layer, and an overlay hydrophobic protective layer. The base layer is sprayed on the surface of the blind blades according to the method of Scheme 3 in Example 1, allowed to stand for 15 minutes, baked at 230°C for 20 minutes, and cured to form a base layer; then, according to the method of Scheme 1 in Example 2, the optical functional layer mixture is sprayed on the surface of the base layer, allowed to stand for 20 minutes, baked at 230°C for 20 minutes, and cured to form an optical functional layer; then, according to the method of Scheme 3 in Example 3, the overlay hydrophobic protective layer mixture is sprayed on the surface of the optical functional layer, allowed to stand for 20 minutes, and baked at 230°C for 20 minutes, to form an overlay hydrophobic protective layer.

[0299] Comparative Example 9

[0300] The present embodiment provides a graded metamaterial structure coating, including a base layer, an optical functional layer, and a top hydrophobic protective layer. The base layer is sprayed on the surface of the blind blade according to the method of Scheme 3 in Example 1, allowed to stand for 15 minutes, baked at 230°C for 20 minutes, and solidified to form a base layer; then, according to the method of Scheme 5 in Example 2, the optical functional layer mixture is sprayed on the surface of the base layer, allowed to stand for 20 minutes, baked at 230°C for 20 minutes, and solidified to form a optical functional layer; then, according to the method of Scheme 3 in Example 3, the top hydrophobic protective layer mixture is sprayed on the surface of the optical functional layer, allowed to stand for 20 minutes, and baked at 230°C for 20 minutes, to form a top hydrophobic protective layer.

[0301] The reflectivity and emissivity of the graded metamaterial structure coatings of Examples 4 to 20 and Comparative Examples 1 to 6 after assembly into a cooling window are shown in Table 1 below.

[0302] Table 1 - Reflectivity and emissivity of the temperature-reducing window assembled from graded metamaterial structure coatings in different embodiments

[0303]

[0304]

[0305]

[0306] The transparent window interlayer and light green tempered glass window interlayer in the above table indicate Figure 2 As shown, the blinds are located between the first glass and the second glass; the outside of the transparent glass window and the outside of the light green tempered glass window indicate that Figure 3 As shown, the shutter is located on the second glass side.

[0307] According to the comparison between Examples 4-6 and Comparative Examples 3-5, it can be seen that the reflectivity of Examples 4, 5 and 6, in which the internal particles are graded and adjusted, is significantly higher than that of Comparative Examples 3, 4 and 5, which are not graded or less graded, proving that the graded structure coating has a stronger ability to reflect solar radiation, that is, a stronger potential for regulating indoor temperature. In addition, it can be seen from Example 4 compared with Examples 5 and 6 that in addition to graded regulation of particle size, the reflectivity of the coating can be further improved by adjusting the mass fraction of particles at different thickness positions.

[0308] It can be seen from Examples 7-18 and Comparative Examples 6 and 7 that by adding corresponding inorganic scattering particles to the bottom layer and the top hydrophobic protective layer, the overall reflection efficiency can be further improved, and the highest reflectivity reaches more than 96%. It can be seen from Example 17 and Comparative Example 8 that whether the blinds are placed in the glass interlayer or outside the window, they can achieve higher sunlight reflection characteristics and mid-infrared emission characteristics, that is, their function of regulating indoor temperature still exists; it can be seen from Example 19 and Comparative Example 9 that when the glass has color, its reflection characteristics are basically unaffected, which shows the wide range of hard work scenes of the blinds.

[0309] Two sentry boxes with a height of 2m and a width and length of 1m were used as experimental objects to verify the effectiveness of the blinds. Both sentry boxes had only one south-facing window of 1m×0.8m. One of the sentry boxes used the ordinary aluminum blinds in Comparative Example 2 without a graded structure, and the other used the blinds with the graded metamaterial structure coating prepared in Example 20 of the present invention. Both blinds were in a completely closed state. The room temperature in the sentry boxes using the two types of blinds was recorded during the period of 11:00am to 14:30pm when the sun was the strongest. The results are as follows: Figure 5 As shown, Figure 5 The medium ambient temperature refers to the ambient temperature outside the booth. Figure 5 It can be seen that compared with the indoor temperature of the booth using ordinary blinds, the internal temperature of the booth using blinds with graded structure coatings is reduced by about 8.05℃, indicating that the graded structure coating has a more obvious cooling effect.

[0310] Figure 6 The cross-sectional SEM image of the graded metamaterial structure coating observed with Example 17 as the sample and the distribution of Ti element in the interface direction show that the Ti element content shows obvious graded characteristics in the coating thickness, proving that the graded metamaterial structure mentioned in the present invention can be stably prepared and can be applied.

[0311] Further, the performance of the graded metamaterial structure coating in Example 17 was tested, and the results were as follows: a cross-cut test was performed based on GB / T9286-2021, and the adhesion was found to be level 1; an impact resistance test was performed based on HGT 4341-2012, and there were no wrinkles, cracks, or peeling after an impact of a 1kg hammer at a height of 50cm; a wash resistance test was performed based on GB / T 9755-2014, and the paint film was not damaged after 5000 washes; an acid salt spray test was performed based on GB / T 10125-2021, and there was no red rust on the surface after 200 hours of acetic acid salt spray; an acid resistance test was performed based on HG / T 4341-2012, and there was no abnormality after 168 hours of immersion in 5% sulfuric acid solution; and a wash resistance test was performed based on GB / T Alkali resistance test was conducted based on GB / T9755-2014, and no abnormality was found in the 48-hour NaOH saturated solution immersion test; artificial weathering was conducted based on GB / T9755-2014, 1000W solar spectrum band irradiation (including 60W 300-400nm UV band irradiation), and no bubbles or cracks were found in the 2000-hour artificial weathering. The windows can meet the needs of long-term use.

[0312] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above-described embodiments only express several implementation methods of the present application, and the description is relatively specific and detailed, but it cannot be understood as a limitation on the scope of the present application. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several deformations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.

Claims

1. A high-irradiation resistant cooling window with a graded metamaterial structure coating, characterized in that: The high-radiation resistant cooling window comprises: a first glass, a second glass, a shutter and two window frames; The first combination of the high-radiation resistant cooling window is a first glass, a second glass, a shutter and two window frames, the first glass and the second glass are arranged at intervals, the shutter is located between the first glass and the second glass, and the first glass, the second glass and the shutter are all fixed between the two window frames; The second combination of the high-irradiation resistant cooling window is a first glass, a second glass, a shutter and two window frames, wherein the first glass and the second glass are arranged at intervals, the shutter is located outside the second glass or the first glass, and the first glass, the second glass and the shutter are all fixed between the two window frames; At least one graded metamaterial structure coating is integrated on the surface of the shutter or window frame. The hierarchical metamaterial structure coating comprises a bottom layer, an optical functional layer with a microscopic hierarchical micro-nano structure, and a top hydrophobic protective layer stacked in sequence; The optical functional layer with microscopic hierarchical micro-nano structure comprises a first high molecular polymer and a first high refractive index inorganic spectral particle filler.

2. The high-irradiation resistant cooling window with a graded metamaterial structure coating according to claim 1, characterized in that: One side surface of the bottom layer is bonded to the surface of the window frame or the shutter blade, and the other side surface is bonded to the optical functional layer of the microscopic hierarchical micro-nano structure; The bottom layer comprises an organic second macromolecular polymer and a functional filler; The second high molecular polymer includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polychlorotrifluoroethylene, acrylic resin, epoxy resin, polyurethane, polyester resin, vinyl resin and silicone resin; The functional filler includes an anti-corrosion filler and a second high refractive index inorganic spectral particle; The anti-corrosion filler comprises at least one of zinc powder, hexasodium phosphate, ferric oxide, zinc phosphate and aluminum tripolyphosphate; The second high-refractive inorganic spectral particle filler includes at least one of titanium dioxide, silicon dioxide, barium sulfate, aluminum oxide, zinc oxide, silicon carbide, zinc sulfide, boron nitride, magnesium oxide, barium carbonate and aluminum silicate.

3. The high-irradiation resistant cooling window with a graded metamaterial structure coating according to claim 1, characterized in that: The first high molecular polymer includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polychlorotrifluoroethylene, acrylic resin, epoxy resin, polyurethane, polyester resin, vinyl resin and silicone resin; The first high-refractive inorganic spectral particle filler comprises at least one of titanium dioxide, silicon dioxide, barium sulfate, aluminum oxide, zinc oxide, silicon carbide, zinc sulfide, boron nitride, magnesium oxide, barium carbonate and aluminum silicate; The mass fraction of the first high-refractive inorganic spectral particle filler in the optical functional layer is 20 to 50%; The particle size of the first high-refractive inorganic spectral particle filler is 10nm to 5000nm; Inside the optical functional layer with microscopic hierarchical micro-nano structure, in the thickness direction, the size of the first high refractive index inorganic spectral particle filler is distributed in a regular pattern from large to small or from small to large; Or, inside the optical functional layer with the microscopic hierarchical micro-nano structure, in the thickness direction, the volume fraction of the first high refractive index inorganic spectral particle filler is distributed in a regular pattern from large to small or from small to large.

4. The high-irradiation resistant cooling window with a graded metamaterial structure coating according to claim 1, characterized in that: The overlay hydrophobic protective layer comprises a third high molecular weight polymer and a hydrophobic filler, and a third high refractive inorganic spectral particle filler; The third high molecular polymer includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polychlorotrifluoroethylene, acrylic resin, epoxy resin, polyurethane, polyester resin, vinyl resin and silicone resin; The hydrophobic filler includes at least one of a silane coupling agent, an organic silicon resin, and nano silicon dioxide. The third high-refractive inorganic spectral particle filler includes at least one of titanium dioxide, silicon dioxide, barium sulfate, aluminum oxide, zinc oxide, silicon carbide, zinc sulfide, boron nitride, magnesium oxide, barium carbonate and aluminum silicate; The mass fraction of the third high-refractive inorganic spectral particle filler in the overcoat hydrophobic protective layer is 5 to 10%; The thickness of the optical functional layer of the microscopic hierarchical micro-nano structure is 50 μm to 200 μm; The thickness of the bottom layer is 10 μm to 100 μm; The particle size of the second highest refractive index inorganic spectral particles in the bottom layer is 10nm to 5000nm; The particle size of the anti-corrosion filler is 200nm to 5000nm; The thickness of the hydrophobic protective layer on the cover surface is 5 μm to 100 μm; The particle size of the third high-refractive inorganic spectral particle filler in the overcoat hydrophobic protective layer is 10nm to 5000nm.

5. The high-irradiation resistant cooling window with a graded metamaterial structure coating according to claim 1, characterized in that: The bottom layer, the optical functional layer with microscopic hierarchical micro-nano structure, and the top hydrophobic protective layer also include a diluent, and the diluent is xylene; The bottom layer includes a second high molecular polymer and a xylene diluent, the second high molecular polymer includes a fluororesin and an acrylic resin, and the mass ratio of the fluororesin, the acrylic resin, and the xylene is (15-20): (5-10): (25-35); Or, the bottom layer includes a second high molecular polymer, an anti-corrosion filler, and xylene, the second high molecular polymer includes fluororesin and acrylic resin, the mass ratio of the fluororesin, acrylic resin, xylene, and anti-corrosion filler is (15-20): (5-10): (25-40): (60-75); the anti-corrosion filler is zinc powder; the particle size of the anti-corrosion filler is 200nm-5000nm; Or, the bottom layer includes a second high molecular polymer, an anti-corrosion filler, xylene, and a second high refractive index inorganic particle, the second high molecular polymer includes a fluororesin and an acrylic resin, the mass ratio of the fluororesin, the acrylic resin, the xylene, the anti-corrosion filler, and the second high refractive index inorganic particle is (15-20): (5-10): (25-40): (60-75): (5-10); the second high refractive index inorganic particle is titanium dioxide, and the particle size of the second high refractive index inorganic particle is 100nm-500nm.

6. The high-irradiation resistant cooling window with a graded metamaterial structure coating according to claim 1, characterized in that: The optical functional layer with microscopic hierarchical micro-nano structure includes a plurality of mutually superimposed sub-optical functional layers, each of which includes a first high molecular polymer, a first high refractive index inorganic spectral particle, and xylene, wherein the first high molecular polymer includes a fluororesin and an acrylic resin, and the particle size and mass ratio of the first high refractive index inorganic spectral particle in different sub-optical functional layers are different; The first high refractive index inorganic spectral particles include at least one of titanium dioxide with a particle size of 100nm to 500nm, titanium dioxide with a particle size of 500nm to 800nm, and titanium dioxide with a particle size of 800nm ​​to 1400nm; The mass ratio of the fluororesin, acrylic resin, xylene and the first high refractive index inorganic spectral particles is (55-65): (15-25): (60-70): (10-80).

7. The high-irradiation resistant cooling window with a graded metamaterial structure coating according to claim 1, characterized in that: The overlay hydrophobic protective layer comprises a third high molecular weight polymer and xylene, wherein the third high molecular weight polymer comprises a fluororesin and an acrylic resin, and the mass ratio of the fluororesin, the acrylic resin, the xylene and the hydrophobic particles is (55-65): (15-25): (70-80): (10-25); Or, the cover hydrophobic protective layer includes a third high molecular weight organic polymer, xylene, and a third high refractive index inorganic spectral particle filler, the third high molecular weight organic polymer includes fluororesin and acrylic resin, and the mass ratio of the fluororesin, acrylic resin, xylene, and the third high refractive index inorganic spectral particles is (55-65): (15-25): (70-80): (10-25): (15-20); the third high refractive index inorganic spectral particles are aluminum oxide with a diameter of 100nm to 300nm.

8. The high-irradiation resistant cooling window with a graded metamaterial structure coating according to claim 1, characterized in that: The optical functional layer with microscopic hierarchical micro-nano structure is composed of two sub-optical functional layers, namely, a bottom optical functional layer and an upper optical functional layer, from bottom to top; Wherein, the first high refractive index inorganic spectral particles in the upper optical functional layer are titanium dioxide with a particle size of 100nm to 500nm; The first high refractive index inorganic spectral particles in the bottom optical functional layer are titanium dioxide with a particle size of 500nm to 800nm; Or, the optical functional layer with microscopic hierarchical micro-nano structure includes three sub-optical functional layers, an upper optical functional layer, a middle optical functional layer, and a bottom optical functional layer, from bottom to top; The first high refractive index inorganic spectral particles in the upper optical functional layer are titanium dioxide with a particle size of 100nm to 500nm; The first high refractive index inorganic spectral particles in the middle optical functional layer are titanium dioxide with a particle size of 500nm to 800nm; The first high refractive index inorganic spectral particles in the bottom optical functional layer are titanium dioxide with a particle size of 800nm ​​to 1400nm; Or, the first high refractive index inorganic spectral particles in the optical functional layer include a mixture of titanium dioxide with a mass ratio of (3-7): (1-3): (1-3) with particle sizes of 100nm-500nm, 500nm-800nm, and 800nm-1400nm respectively.

9. A method for preparing a high-irradiation resistant cooling window with a graded metamaterial structure coating according to any one of claims 1 to 8, comprising the following steps: The first glass, the second glass, and the blinds are all installed between the window frames to obtain a cooling window with a high-radiation-resistant coating having a graded metamaterial structure; Wherein, at least one graded metamaterial structure coating is integrated on the surface of the shutter or window frame; The method for preparing the hierarchical metamaterial structure coating comprises the following steps: Adding optional second high refractive index inorganic spectral particles, optional anti-corrosion filler, and optional diluent to the second high molecular polymer, stirring and mixing, to obtain a bottom layer mixture; Apply the primer mixture to the surface of the window frame or shutter blades to form a primer; Adding a first high refractive index inorganic spectral particle filler with different physical properties and an optional diluent into a first high molecular polymer, stirring and mixing, to obtain a plurality of spectral functional mixtures; Applying a plurality of spectral functional mixtures in sequence on the surface of the bottom layer to form a light functional layer with a microscopic hierarchical micro-nano structure; Adding the optional third high-refractive inorganic spectral particles, hydrophobic material, and optional diluent to the third high molecular weight polymer, stirring and mixing, to obtain a surface hydrophobic protective layer mixture; The surface hydrophobic protective layer mixture is coated on the surface of the optical functional layer with microscopic graded micro-nano structure to form the surface hydrophobic protective layer.

10. An application of the high-irradiation resistant cooling window with a graded metamaterial structure coating according to any one of claims 1 to 8 or the high-irradiation resistant cooling window with a graded metamaterial structure coating prepared by the preparation method according to claim 9 in office buildings, factories, residential buildings, sentry boxes, mobile homes, glass curtain walls, exhibition halls and commercial centers, as well as cars, trains, airplanes, ships and yachts, as well as space capsules, drones, armored vehicles, fighter jets and helicopters.

Citation Information

Patent Citations

  • Cooling product and preparation method of full-solar-spectrum high-reflection fabric

    CN115593062A

  • Heat insulation color steel tile and preparation method thereof

    CN116104253A

  • Preparation method and application of passive cooling photo-thermal regulation fiber and fabric

    CN117488423A

  • Multifunctional solar thermoelectric comprehensive utilization energy-saving window

    CN114033280A

  • Photo-thermal regulation and control energy-saving window

    CN118481483A